Privacy, Security, and Ethics in Technology: A Qur'anic Perspective Through Cybercrime - Septi Aisyah; Muhammad Farhan Bin Mat Noradin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The rapid advancement of technology has significantly facilitated human activities, particularly in communication. However, technology is often misused for unethical and criminal purposes, such as theft, spreading misinformation, hate speech, and various forms of fraud. This study employs a literature research method with a maudhui approach based on Al-Farmawi’s framework. The findings indicate that the Qur'an provides clear guidance on privacy, security, and ethical principles in the use of technology. These principles serve as a foundation for addressing contemporary issues, including cybercrime, from an Islamic perspective. The study underscores the relevance of Qur'anic values in mitigating the ethical dilemmas posed by technological advancements. For future research, it is recommended to explore the practical implementation of Qur'anic ethical principles in digital policies and cybersecurity frameworks. Additionally, empirical studies on the effectiveness of Islamic ethics in preventing cybercrimes, as well as comparative analyses between Qur’anic perspectives and modern cybersecurity regulations, could provide further insights into developing ethical and secure digital environments.